2019
DOI: 10.1111/apa.14709
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental difficulties negatively affect health‐related quality of life in children with idiopathic clubfoot

Abstract: Aim: To study health-related quality of life (HRQoL) in children with idiopathic clubfoot (IC) and the influence of sex, clubfoot laterality and neurodevelopmental difficulties (NDD) on HRQoL. Methods: A cross-sectional questionnaire-based study in Stockholm and Sk ane Counties, Sweden, of 106 children with IC born 2004-2007 (mean 9.4 AE 0.6 years) and a general population sample of 109 schoolchildren (mean 9.5 AE 0.6 years). The children and their caregivers answered the EQ-5D-Y (Youth) and Five to Fifteen qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Indeed, recent evidence raised the hypothesis that isolated clubfoot is not only a disorder of the musculoskeletal system but may be associated with neurodevelopmental difficulties. [21][22][23] Despite the reason behind this association remains to be determined, we can speculate that clubfoot could be a part of genetic syndromes, evidenced by the present study.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Indeed, recent evidence raised the hypothesis that isolated clubfoot is not only a disorder of the musculoskeletal system but may be associated with neurodevelopmental difficulties. [21][22][23] Despite the reason behind this association remains to be determined, we can speculate that clubfoot could be a part of genetic syndromes, evidenced by the present study.…”
Section: Discussionmentioning
confidence: 53%
“…The remaining 38 had isolated clubfoot and were included in this study. For those, the median MA was 26 (range: 20-46) years old, and the median GA at diagnosis was 22 (range: [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] weeks. Through the trio-ES analysis, pathogenic or LP variants were detected in four of 38 fetuses (Table 1) within the following genes: BRPF1, ANKRD17, FLNA and KIF1A.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Smith et al found that children who underwent surgery to treat clubfoot reported more pain than children who underwent Ponseti treatment; however, both groups were functional and had a high quality of life [27]. Causes of decreased quality of life in these patients include prolonged use of braces and consequent inability to play and anxiety and discomfort caused by thinking of others about how they walk [5,28].…”
Section: Discussionmentioning
confidence: 99%
“…Study 3: Lööf et al (2018), 20 Neurodevelopmental Difficulties Negatively Affect Health-related Quality of Life (HRQoL) in Children with Idiopathic Clubfoot.…”
Section: Introductionmentioning
confidence: 99%